Glucagon-like peptide-1 receptor agonist and the relation between metabolic effects and cardiovascular outcomes: insight into mechanisms of action. (14th October 2021) - Di Ienno, L; Serenelli, M; De Carolis, B; Cantone, A; Buccino, N; Tolomeo, P; Vitali, F; Guardigli, G; Campo, G
Abstract: Background: Glucagon-like Peptide-1 receptor agonists (GLP-1RAs) have been shown to lower cardiovascular risk, and they are likely to reduce the incidence of all-cause and cardiovascular mortality in patients with type 2 diabetes. In this study-level analysis we investigated how metabolic and blood pressure changes are related to the reduction of cardiovascular events with GLP-1RAs. Methods: We included seven randomized, placebo-controlled trials (ELIXA, LEADER, SUSTAIN-6, REWIND, EXSCEL, PIONEER 6, Harmony Outcomes) reporting incidence of one or more of the following outcomes: MACE, stroke, myocardial infarction, cardiovascular death, all-cause death, for a total of 56004 patients. A Pearson correlation analysis between logHR for the occurrence of outcome and placebo-corrected changes in Hb1Ac, systolic blood pressure and weight was performed. Findings: Reduction of HbA1c level was significantly related to the reduction of MACE, Pearson R 0.86 (p=0.006) and stroke, Pearson R 0.79 (p=0.018). The reduction of weight instead, showed a robust correlation, not only with reduction of MACE, Pearson R 0.75 (p=0.032) and stroke, Pearson R 0.71 (p=0.047), but also with reduction of both cardiovascular death, Pearson R 0.95 (p=0.003; Picture 1) and all-cause death, Pearson R 0.91 (p=0.013). Reduction of SBP was significantly related to the reduction of both cardiovascular death, Pearson R 0.84 (p=0.036) and all-cause death, Pearson R 0.88 (p=0.020), but not of MACE. Discussion: Mechanism of GLP-1RAs in preventing MACE is not fully understood. Other drugs that improve glycemic control did not showed convincing effect on cardiovascular outcome. Our finding prompts some considerations: both weight loss and control of HbA1c levels could play a role in MACE reduction. On the other hand, GLP1-RAs could act through other mechanisms and the metabolic effect could be a marker of the drug potency and dosage. Based on mechanistic studies, a theorized mechanism of cardiovascular benefit seen with GLP-1 RA is thought to be an anti-atherothrombotic and lipid plaque stabilization effect. This seems particularly convincing seeing the strong relationship of weight change and major events reduction. Notably, reduction in cardiovascular mortality and all-cause mortality was not related to the anti-hyperglycemic effect. Contrarily the body weight and SBP reduction were strongly related to both cardiovascular and all-cause mortality. These features could support the presumption of a hypothetic GLP1-RAs mechanism in modulation of lipidic profile and in RAAS inhibition, which have been already proved as beneficial for primary and secondary cardiovascular prevention. Conclusion: Cardiovascular protection from GLP1-RAs is not primarily related to HbA1c reduction itself. Our data suggest that GLP-1RAs with the greater metabolic impact, such as liraglutide and semaglutide, should be used to treat diabetic patients to prevent MACE and CV death. FUNDunding Acknowledgement: Type of funding sources: None.